Managing innovation : integrating technological, market and organizational change - Tidd, Joseph, 1960-; Bessant, J. R (Chichester, England : John Wiley & Sons, 2009)
Managing Innovation is an established, bestselling text for MBA, MSc and advanced undergraduate courses on management of technology, innovation management and entrepreneurship. It is also used widely by managers in both the service and manufacturing sectors.
Includes bibliographical references and index.
Keywords: Technological innovations -- Management; Industrial management; Organizational change